APLIKASI SEPASAR SEBAGAI PLATFORM EDUKASI HYBRID UNTUK MENINGKATKAN KAPASITAS PEDAGANG PASAR BERINGHARJO DI MASA PANDEMI COVID-19 - Sumiyarsih, Sumiyarsih; Wahyuningsih, Tri Harsini; Subarjo, Subarjo; Santosa, Awan (Abimanyu : Jornal of Community Engagement, 2023)
Beringharjo Market is the largest traditional market in Yogyakarta owned by the Yogyakarta city government . Beringharjo Market is one of the markets affected by the Covid-19 pandemic so that this situation makes it difficult for market traders to serve consumers who usually gather at the stalls or market booths and make sales. The number of buyers decreased quite a lot and happened a decrease in visits from tourists by up to 70 percent. This condition resulted in approximately 5000 traders and 300 carrying workers experiencing negative impacts due to the Covid-19 outbreak. Based on these problems, the solution is the Sepasar application as a Hybrid Education and Online Marketing media. Sepasar as a solution to the problems faced by providing online courses according to the needs of Beringharjo market traders . The Sepasar application also helps increase sales for Beringharjo Market Merchants by promoting products, events, and services. Expected output targets from the joint community empowerment program Sepasar is existence enhancement knowledge, skills , HR and organizational capacity, as well as digital literacy of Beringharjo market traders in using various digital media that help them in marketing, finance and organizational management .